Linking innovations systems with participatory research and extension: MIRACLE experiences from southern Africa - Ellis-Jones, J.; Gondwe, T.N.P. (2013)
MIRACLE (“Making innovations work for smallholder farmersaffected by HIV and AIDS in southern Africa”) brings togetherkey stakeholders in operational and strategic level innovationplatforms. This paper outlines MIRACLE’s strategy forimproving livelihoods through improved production, processing,consumption and marketing of nutritionally-enhanced crops.Operating in Malawi, Mozambique, Swaziland and Zambia,MIRACLE brings together researchers, NGOs, public extension,local leaders, community based organisations (CBOs), farmersand the private sector. MIRACLE’s four-stage ParticipatoryResearch and Extension Approach (PREA) involves communityengagement and social mobilization, action planning,experimentation, learning and sharing experiences.The paper highlights early achievements and challenges andidentifies key lessons. These include the need for building andsupporting partnerships, strengthening farmer organisationsto participate in research, accessing existing knowledge andfostering learning. A well organised private agri-businesssector is essential for developing market opportunities, capacitybuilding and engaging with the public and NGO sectors.Sustainability will be built on local ownership with effectiveback-up from R&D organisations in both private and publicsectors. Scaling up successful pilot initiatives can be supportedby strategic level innovation platforms (IPs) linked to andinteracting with local operational IPs.